Regulating for a sustainable and resilient single market: Challenges and reforms in the areas of state aid, competition, and public procurement law - Marta Andhov; Andrea Biondi; Luca Rubini (European Trade Union Institute (ETUI), 2023)
The single market currently sits at the centre of the European economic integration project and plays a key role in the EU processes of political and social integration.This centrality would have been purely totemic had it not been for the inherent success and resilience of the European integration project. Over the past 30 years, the single market has survived several crises largely unscathed: economic ones (including various recessions and austerity-driven downturns), political ones (Brexit comes immediately to mind) and, more recently, a pandemic and a violent armed conflict virtually on its doorstep. While undoubtedly still a 'project', and far from being fully accomplished let alone finalised, the single market has consolidated its role as the central Weltanschauung of the European Union. For the most part, the picture that the authors, law professors Marta Andhov, Andrea Biondi and Luca Rubini, have painted for us is one of progressive incrementalism in the EU's efforts to bolster the contribution that the single market rules covered by their analysis make to the ecological, social and industrial sustainability dimensions of the European project. Readers of this report, and of the three papers produced by our experts, will undoubtedly feel enriched by the sophisticated and detailed analysis of the - often untapped - potential offered by these recent, ongoing reforms. Reforms that, as the authors point out, are carefully balancing both the social and the competitiveness rationales sustaining the Treaty formula for a 'highly competitive social market economy'.
Keywords: 330; EU-Binnenmarkt; Europäische Integration; EU-Staaten